The era of genome editing: current updates and the status of food and nutrition security - Khaled, Fathy; Mehta, Sahil; Agrawal, Pawan Kumar; Abdel-Monem, Usama M.; El-Akkad, Hend; Gendy, Ahmed S.; Al-Maracy, Sherin H. A.; Heakel, Rania M. Y.; Wafa, Hany A.; Fathy, Rania; Narayan, Om Prakash (Frontiers in Sustainability, 2024)
Food security is the situation in which all people around the globe, in all circumstances must maintain constant physical and financial , ensuring consistent global access to adequate nutritious, clean, and safe food. This is why food security is regarded as , is a major global issue. Domestically and internationally, many critical concern shaped by factors affect food production and quality; these include environmental such as climate change conditions, disasters, emerging new diseases, political issues, and economic shifts in the global economy.Additionally, rapid. Rapid population growth necessitates adjustments toin food and crop production. The, but current agricultural production strategies negatively affectadversely impact soil fertility and cause many defects such as desertification, deforestation, and increased soil salinity. Additionally, the high use of chemical fertilizers and pesticides affects human health and food production. The production of numerous strategicthrough agrichemical use. Strategic crops, including like rice, maize, soybeans, and wheat, was face reduced dueproduction, contributing to the aforementioned factors. Thea global rise in the hunger index increased, and millions of people were placed in the and hidden hunger. Efforts